The contribution of community pharmacy to improving the public's health. Report 1, Evidence from the peer-reviewed literature 1990–2001 - Anderson, Claire; Blenkinsopp, Alison; Armstrong, Miriam (PharmacyHealthLink and the Royal Pharmaceutical Society of Great Britain, 2003)
The modernisation of the NHS has highlighted the Government's intent to improve the public’s access to health services, information on preventing ill health and support for self-care. Community pharmacies are in a strong position to contribute to this agenda with around 12 000 dedicated premises in the UK creating an informal network of ‘drop in’ access points for health care services, medicines and advice on health and well-being. It has been estimated that over six million people visit pharmacies every day. Many pharmacy staff work in premises that are sited within local communities and shopping precincts where they provide easy access to the public without the need for an appointment. The informal nature of contact with a pharmacy creates an experience for users which is more similar to a ‘consumer’ than as a ‘patient’. Visitors to pharmacies come from all sectors of the population and research has shown that local pharmacy services are particularly valued by those without easy access to a car or public transport. In recognition of this potential the recent Health Committee Inquiry into Public Health5 recommended that ‘the Government takes steps for community pharmacists to play a more active role in public health’. As a result of these characteristics there is an opportunity for pharmacy staff to give advice and support on health or medicines to a significant proportion of the population on a regular or ad hoc basis. Much of this advice is given with prescriptions and the treatment of minor illnesses, however, some pharmacies also provide other services to improve health, such as help with smoking cessation, dietary advice, and testing of blood pressure and cholesterol. The provision of these latter services, however, is not universal and there has been no systematic evaluation of the evidence on their contribution to public health. To help assess the value of these services delivered through pharmacy, the Royal Pharmaceutical Society of Great Britain (RPSGB)and the charity PharmacyHealthLink commissioned a review of the UK and international evidence-base health improvement in order to determine which activities are most likely to be effective in a pharmacy setting and how they might best be provided. The review demonstrates that certain services are both sufficiently well-researched and well-received by pharmacy users at an international level, for example in smoking cessation, lipid management in the prevention of coronary heart disease, immunisation and emergency contraception, that recommendations for their widespread implementation in the UK can be made. Other services also show promise but are less wellresearched and require more evaluation before an assessment of their effectiveness and suitability in a pharmacy setting can be determined. This review can help to shape the contribution of community pharmacists to a modernised health service. It provides useful evidence to those involved in the planning and provision of health services to prevent illness and maintain health. Funding bodies and commissioners may wish to use its findings to develop pharmacy services to contribute further to their health improvement plans and local targets.